Keefektifan Paired Story Telling Terhadap Keterampilan Menyajikan Teks Deskripsi - Bustamin Bustamin; Eka Alwiah Haseng (Jurnal Ilmiah Multidisiplin Amsir, 2025)
Presenting text is a language skill that is generally recognized so that it requires good language skills. Not only good language skills, in presenting text skills also require mastery of spelling, grammar rules, standard grammar, and effective sentences. Students are expected to be able to organize data and facts into a paragraph. After students receive the media provided, students should be able to take the things they need and use them as material to present descriptive text. The data and facts obtained by students must be arranged so that they can become good paragraphs. While until now students are still lacking in arranging the data and facts they have to become correct descriptive paragraphs. One effort to create a learning atmosphere for interactive, inspiring, active and fun descriptive text presentation activities. This study aims to make the Indonesian language learning process effective using Paired Story Telling. The research method used is pre-experimental design research. The results of this study Paired Story Telling on the skills of presenting descriptive texts of class VII students of SMP Negeri 2 Satap Mambi are shown through the Paired Sample Test table, obtained a t-count value of -15.541 and a t-table value of 2.845 with a degree of freedom (df) of 20, and a 2-tailed significance of 0.00. The significance value obtained is smaller (<) than alpha (α) 0.05. This is interpreted that Paired Story Telling is effectively applied to the material of presenting descriptive texts